LENS PROTEOMICS: EXPLORING ADAPTIVE CONFLICT IN UROMASTYX HARDWICKII LENS PROTEINS - A. Atta; Z. Hashim; S. Zarina (Journal of Animal and Plant Sciences, 2016)
During last decade, proteomics has emerged as a powerful tool for high throughput screening, identification and quantification of proteins from biological samples. In current study, we have employed proteomics technique to explore proteins from eye lenses of Uromastyx hardwickii, an Indian spiny-tailed lizard. Water soluble and insoluble proteins from Uromastyx hardwickii lens were separated and characterized by 2-DE (two dimensional electrophoresis). After in-gel digestion, well resolved spots were identified by nano- liquid chromatography-electrospray tandem mass spectrometry (nLC-MS/MS). We have identified αA-, βA2-, βA4-, βB2- and βB3-crystallins as ubiquitous crystallins and δ-, τ-crystallins as taxon-specific lens crystallins in water soluble fraction. αA- and βB3-crystallins were found to be most abundant water soluble proteins in Uromastyx hardwickii lens. Among non-crystallins (cellular proteins), β-actin was identified. From water insoluble fraction, vimentin, gelsolin, gamma enolase like protein, filensin like protein and ATP synthase subunit B were identified. Our results illustrate advantage of proteomics technology for identification of lens proteins. Furthermore, the study provides distribution patterns of ubiquitous and taxon specific crystallins from Uromastyx hardwickii that is likely to be useful in understanding evolutionary lineage of this organism.
Keywords: Lens proteomics; ubiquitous lens crystallin; taxon specific lens crystallin; Uromastyx hardwickii; water insoluble lens protein